2019
DOI: 10.1016/j.jor.2019.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction - A comparison between patient-specific implants and conventional total knee arthroplasty

Abstract: Background: Despite recent innovations in total knee arthroplasty, 20% of the patients are not completely satisfied with the clinical results. Regarding patient-specific implants (PSI), the study aims to compare individual and off-the-shelf implant (OSI) total knee arthroplasty (TKA) concerning the postoperative outcome like function and global patient satisfaction. Methods: In 2013/14 228 patients received a TKA due to primary osteoarthritis with an indication for a bicondylar, cruciate retaining prosthesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 27 publications
(33 reference statements)
6
56
0
Order By: Relevance
“…Very few studies have reported clinical outcomes after custom implants. Reimann et al described that the patient-specific implants might increase patient satisfaction at 2 years [ 20 ]. Schwarzkopf et al and White et al, found no significant difference in clinical outcomes, with only a tendency to decreased range of motion [ 21 , 22 ].…”
Section: Individual Knee Arthroplasty Implantmentioning
confidence: 99%
“…Very few studies have reported clinical outcomes after custom implants. Reimann et al described that the patient-specific implants might increase patient satisfaction at 2 years [ 20 ]. Schwarzkopf et al and White et al, found no significant difference in clinical outcomes, with only a tendency to decreased range of motion [ 21 , 22 ].…”
Section: Individual Knee Arthroplasty Implantmentioning
confidence: 99%
“…In contrast, Schwarzkopf et al [ 24 ] reported a decrease of 3.44° (range, −83° to 55°) in ROM after TKA with PSI, whereas patients receiving OTS implants showed an increase of 1.54° (range, −80° to 90°, p < 0.1). The remaining authors did not observe statistically significant differences in ROM between both groups [ 20 , 22 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 97%
“…The literature search yielded a total of 1430 publications and, after allocation processes shown in Figure 1 , 13 articles met the criteria for this systematic review. Of these articles, 11 investigated the outcomes after TKA [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and two investigated the outcomes after UKA [ 27 , 28 ] with PSI versus OTS implants. There were four prospective cohort studies and nine retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…There is now over a decade of experience with customized implants, including over 100,000 implantations worldwide. Previous peer-reviewed studies confirm that patient specific TKA implants provide improved fit and alignment 9,10,11,12 , better kinematic function 13,14 , reduced short-term complication rates 15,16 , higher patient satisfaction 17,18 , and overall cost savings 15,16,19,20 when compared to standard off the shelf implants. Data from the UK National Joint Registry (UKNJR), recently released by Beyond Compliance, highlight a lower cumulative revision rate for the custom cruciate retaining implants than that of all other knee implants in the UKNJR 21 .…”
Section: Custom Implants and Toolsmentioning
confidence: 94%